Kajian Teori Supervisi Pendidikan Dalam Islam (Perspektif Al-Qur’an dan Hadits) - Diba, Ishlah Farah; Gunawan, Agus (STAI Denpasar Bali, 2023)
Educational supervision in the Qur'an generally approaches supervision (controlling). Allah SWT is the best, very detailed and perfect supervisor of what is hidden in the hearts of His servants. Meanwhile, supervision in the Hadith of Rasulullah SAW uses various methods, adapting to the situation and conditions of the friends. This research method uses the literature research method, namely a literature study approach to search for and collect literature related to educational supervision in Islam. The focus of this article is 1) Understanding Educational Supervision in Islam, 2) Educational Supervision from the Al-Qur'an Perspective, and 3) Educational Supervision from the Hadith Perspective, and 4) Principles of Educational Supervision in the Al-Qur'an and Hadith. Educational supervision from an Islamic perspective prioritizes a humanistic approach, not just filling in data on paper, not just demanding maximum work. But more on the approach and input of Islamic values ​​related to the Al-Qur'an and Hadith.